Swimming as a Means of Personal Development of Students in the Educational Environment - Grigan S.A.; Lyashko G.I. (Theory and Practice of Physical Culture, 2025)
The problem of forming individual and collective qualities of students in the process of their education and upbringing occupies a central place in pedagogical and psychological research. Particular attention is paid to physical activity as a tool for harmonious personal development. In this context, swimming is considered an effective means of forming key personal qualities. Physical activity is a powerful factor in the development of personal characteristics such as purposefulness, self-control, and stress resistance. Regular sports activities improve cognitive abilities, develop emotional stability, and contribute to the formation of motivation for self-development. The purpose of the study is to analyze the effectiveness of using swimming as a means of personal development in the educational environment. The study involved 60 students who participated in an experiment for a semester (12 weeks) at Rostov State University of Transport. Humanities majors require the development of students' skills in interpersonal interaction, empathy, and communicative competence. Physical education, integrated into the educational process, stimulates the manifestation of qualities such as responsibility, mutual respect, and collectivism. Swimming stands out among other sports for its versatility. Water-based activities contribute to the development of physical endurance, coordination of movements, and psycho-emotional stability. Water creates unique conditions that reduce tension and increase concentration, which is especially important for students under intellectual loads.